Assessment of metabolic syndrome in infertile women with polycystic ovary syndrome in a rural population of South India: A cross-sectional study - Sreelalitha Kayali; Thyagaraju Chitra; Sadishkumar Kamalanathan; Hanumanthappa Nandeesha (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract Background: Polycystic ovary syndrome (PCOS) is known to be associated with metabolic syndrome (MS). It is characterised by insulin resistance, hyperinsulinemia, dyslipidemia, obesity and hypertension. Data related to MS in infertile women with PCOS are limited in Indian populations. Objective: This study aims to compare the prevalence of MS in infertile women with and without PCOS in a rural population in South India. Materials and Methods: 130 women with PCOS and 130 women without PCOS were enrolled in this cross-sectional study. A detailed history was taken and a physical examination was done for all women. Anthropometric parameters, a glucose tolerance test, fasting glucose / insulin levels, trigylcerides, high-density lipoprotein cholesterol and blood pressure were assessed in all participants. The International Diabetes Federation criteria were applied for assessment of MS. Results: MS was more prevalent in infertile women with PCOS (42.3%) compared to women without PCOS (19.3%). 56.9% of women with PCOS had low high-density lipoprotein cholesterol levels, 46.2% had high triglycerides, 71.5% had a high waist circumference, 31.5% had high blood pressure and 37.7% had high blood glucose levels. 26.0% of the women with PCOS had a healthy weight, and MS was seen in 6.9% of these women. Conclusion: The prevalence of MS was higher in women with PCOS in comparison to women without PCOS. Among the women with PCOS, the prevalence of MS increased with age ( > 27 yr), body mass index and waist circumference (71.5%), and even healthy women with PCOS contributed to 7% of MS. Hence it becomes necessary to screen all women with PCOS for metabolic profile risk factors at young age itself to prevent long term cardiovascular complications.